نشرا لطیب فی ذکرالنبی الحبیب ﷺ کاتعارف و منہج؛ ایک تجزیاتی مطالعہ : An Analytical Study of the " Nashr al-Tīb fi Zikr-un-Nabi Al-Habib" - Fakharuddin, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2020)
Sira of the Holy Prophet ﷺ is the only subject that can quench the thirst of every subject in the universe and guarantee the solution of every problem. Love and Obedience to the Holy Prophet (peace and blessings of Allah be upon him) is a must. Mawlana Ashraf Ali Thanwi ranks high in the list of biographers through his famous book "Nashr al-Tīb" in remembrance of the Beloved Prophet (May God bless him and his family and grant them peace) which is comprehensive enough to do its function. The book is one of his excellent works in its own way. It is a valuable book in Urdu language which has been presented in an unparalleled manner. It shows the love of the Holy Prophet ﷺ as well as his teachings; mysteries and secrets which is Narrated in the style of Mathnavi Maulana Rum. In the said article, the introduction and method of " Nashr al-Tīb fi Zikr-un-Nabi Al-Habib" will be presented. In order to know the services and style of writing and purpose of Mawlana in Sira Nigari and the only purpose of Sira Nigari is to achieve love of of the Holy Prophet and obedience to Him ﷺ.